A Proposed Systematic Framework for Applying Hoshin Kanri Strategic Planning Methodology in Educational Institutions - Ahmed, Hanaa Ouda Khadri (European Scientific Journal, ESJ, 2016)
Hoshin Kanri is a methodology that was developed in Japan in the late 1960s. Now, it has become an essential component in numerous institutions that are implementing new management systems and concepts such as Balanced Scorecard (BSC), TQM, and Lean Management or Six Sigma. Hoshin Kanri is a management method used for reinforcing strategic work. In spite of a number of Hoshin Kanri success stories in many sectors and a variety of institutions, little research attention has been given to the implementation of Hoshin Kanri methodology in educational institutions. This research supports an increased focus on Hoshin Kanri methodology in Strategic Planning for educational institutions. The main aim of this paper is to propose a systematic framework for applying Hoshin Kanri strategic planning methodology in educational institutions. In achieving this aim, the meaning and origins of Hoshin Kanri were defined, the foundations of Hoshin Kanri planning methodology were analyzed, the factors influencing the implementation of Hoshin Kanri planning in educational institutions were discussed, and a structured process for implementing Hoshin Kanri planning in educational institutions was developed.